Artistic process promoted by women: Mayan weavers in the highlands of Chiapas - Gil Corredor, Claudia Adelaida (Revista do Colóquio, 2021)
Analytical descriptions of an ancient artistic practice, weaving, carried out by the current Tsotsil and Tseltal Mayan women of Los Altos de Chiapas, are presented based on the notion of agency. The aim is to demonstrate the interrelational nature of the cultural aesthetics of an indigenous people who make weaving a way of life in which they link aspects of their historical heritage with their collective feeling and their daily activities. Likewise, weaving shows the agency of women, who through their activity as weavers become agents of transformation and resistance.